2022
DOI: 10.1007/s11255-022-03277-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes after transplantation of deceased donor kidneys with acute kidney injury: a retrospective analysis of a multicenter cohort of marginal donor kidneys with post-explantation biopsies

Abstract: Background Deceased donor kidneys with acute kidney injury (AKI) are often discarded because of concerns about inferior transplant outcomes. A means of grading the quality of such kidneys is the performance of procurement biopsies. Methods This is a retrospective study of 221 brain death donors with marginal kidneys transplanted in 223 recipients in Germany. Marginal kidneys were defined as kidneys with procurement biopsies done exceptionally to assess sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“… 36 Conversely, a study from Germany analyzed outcomes from donors ≥65 years of age with or without AKI and noted no differences in renal function or survival outcomes (Table 7). 40 Another study from Germany concluded that histopathological assessment of non‐ideal donor kidneys with AKI was not helpful in predicting outcomes 73 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 Conversely, a study from Germany analyzed outcomes from donors ≥65 years of age with or without AKI and noted no differences in renal function or survival outcomes (Table 7). 40 Another study from Germany concluded that histopathological assessment of non‐ideal donor kidneys with AKI was not helpful in predicting outcomes 73 …”
Section: Discussionmentioning
confidence: 99%
“…40 Another study from Germany concluded that histopathological assessment of non-ideal donor kidneys with AKI was not helpful in predicting outcomes. 73 Based on a number of studies from 2005 to 2007 that showed acceptable short-term outcomes with AKI kidneys from highly selected SCDs, and an increasing number of available AKI donor kidneys, we initiated a programmatic change in January 2007 to begin utilizing AKI donor kidneys. [21][22][23]41,42 We have previously reported our experience with AKI donor kidney transplantation with short and long-term follow-up as well as our experience using AKI donor kidneys with prolonged CIT.…”
Section: F I G U R Ementioning
confidence: 99%
“…34 Similarly, none of the studies we summarized in Table 1 have reported increased acute rejection rates in AKI donor recipients. 9,[12][13][14]20,[22][23][24] Furthermore, Budhiraja et al 35 studied the impact of DGF duration on transplant outcomes, and on multivariate analysis, donor AKIN stage of ≥2 was not associated with DGF duration. As such, transitively, worsening AKI stage should not contribute to longer duration of DGF and this should not contribute to increased risk of acute rejection.…”
Section: Immune Activity In Iri and Acute Rejectionmentioning
confidence: 99%
“…As expected, most studies documented higher DGF in deceased donors with AKI. 6,8,9,[12][13][14][15]17,18,20,24 However, there is mixed data in the literature as to the relationship of DGF to short-and longterm graft outcomes, allograft function, and acute rejection.…”
Section: Clinical Outcomes: Delayed Graft Functionmentioning
confidence: 99%
See 1 more Smart Citation